External Ventricular Drain Infections: Risk Factors and Outcome. (17th November 2014) - Hagel, S.; Bruns, T.; Pletz, M. W.; Engel, C.; Kalff, R.; Ewald, C.
Abstract : External ventricular drainage (EVD) is frequently used in neurosurgery to drain cerebrospinal fluid in patients with raised intracranial pressure. We performed a retrospective single center study in order to evaluate the incidence of EVD-related infections and to identify underlying risk factors. 246 EVDs were placed in 218 patients over a 30-month period. EVD was continued in median for 7 days (range 1–44). The cumulative incidence of EVD-related infections was 8.3% (95% CI, 5.3–12.7) with a device-associated infection rate of 10.4 per 1000 drainage days (95% CI, 6.2–16.5). The pathogens most commonly identified were coagulase-negative Staphylococcus (62%) followed by Enterococcus spp. (19%). Patients with an EVD-related infection had a significantly longer ICU (11 versus 21 days, P < 0.01 ) and hospital stay (20 versus 28.5 days, P < 0.01 ) than patients without. Median total duration of external drainage was twice as long in patients with EVD-related infection (6 versus 12 days, P < 0.01 ). However, there was no significant difference in the duration between first EVD placement and the occurrence of EVD-related infection and EVD removal in patients without EVD-related infection (6 versus 7 days, P = 0.87 ), respectively. Interestingly no risk factor for EVD-related infection could be identified in our cohort of patients.